Design and Applications of Additive Manufacturing and 3D Printing - Salmi, Mika (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Additive manufacturing (AM), more commonly known as 3D printing, has grown trememdously in recent years. It has shown its potential uses in the medical, automotive, aerospace, and spare part sectors. Personal manufacturing, complex and optimized parts, short series manufacturing, and local on-demand manufacturing are just some of its current benefits. The development of new materials and equipment has opened up new application possibilities, and equipment is quicker and cheaper to use when utilizing the new materials launched by vendors and material developers. AM has become more critical for the industry but also for academics. Since AM offers more design freedom than any other manufacturing process, it provides designers with the challenge of designing better and more efficient products.